Molecular effects of advanced glycation end products on cell signalling pathways, ageing and pathophysiology - Nedić, O.; Rattan, S. I. S.; Grune, T.; Trougakos, I.P. (Free Radical ResearchFree Radical Research, 2013)
Advanced glycation end-products (AGEs) are a heterogeneous group of compounds formed by the Maillard chemical process of non-enzymatic glycation of free amino groups of proteins, lipids and nucleic acids. This chemical modification of biomolecules is triggered by endogeneous hyperglycaemic or oxidative stress-related processes. Additionally, AGEs can derive from exogenous, mostly diet-related, sources. Considering that AGE accumulation in tissues correlates with ageing and is a hallmark in several age-related diseases it is not surprising that the role of AGEs in ageing and pathology has become increasingly evident. The receptor for AGEs (RAGE) is a single transmembrane protein being expressed in a wide variety of human cells. RAGE binds a broad repertoire of extracellular ligands and mediates responses to stress conditions by activating multiple signal transduction pathways being mostly responsible for acute and/or chronic inflammation. RAGE activation has been implicated in ageing as well as in a number of age-related diseases, including atherosclerosis, neurodegeneration, arthritis, stoke, diabetes and cancer. Here we present a synopsis of findings that relate to AGEs-reported implication in cell signalling pathways and ageing, as well as in pathology. Potential implications and opportunities for translational research and the development of new therapies are also discussed. © 2013 Informa UK, Ltd.
Keywords: Ageing; AGEs; RAGE; Signalling; stress